Now everybody is a friend; how native advertising influences Indonesian journalistic field - Indra Prawira; Yusa Djuyandi; Medo Maulianza; Rahmat Edi Irawan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Native advertising is increasingly the primary practice of online news media to gain economic benefits. The nature of native advertising resembling news content is considered effective in influencing the public. The media study in Indonesia focused heavily on media democratization following the authoritarian media system for more than three decades. However, Indonesian media's economic competition is becoming more challenging, and media personnel are looking for new ways to earn money from native advertising. This study investigates the contemporary development of Indonesian journalism concerning the increased native advertising practice. It utilizes the field theory of Pierre Bourdieu's journalistic and journalism social responsibility approach. Data was collected through semi-structured interviews of fifteen personnel from three Indonesian online news media. The study showed that Indonesian online news media highly practice native advertising to earn revenue. The increasing practice of native advertising in Indonesia urges journalists to be involved in advertising content production and dissemination. There is resistance from media personnel in native advertising practice. However, native advertising has become irresistible because most media are in an economic crisis. Native advertising drives media to make friends with every prospective client, including the Government. The media has become less independent and less concerned about their social responsibility as a watchdog because the Government and state apparatus are their clients. The media develop new norms and traditions to accommodate native advertising